Pathways for enhancing sustainable mobility in emerging markets: Cost-benefit analysis and policy recommendations for recycling of electric-vehicle batteries in Thailand - Chaianong, Aksornchan; Pharino, Chanathip; Langkau, Sabine; Limthongkul, Pimpa; Kunanusont, Nattanai (Sustainable Production and Consumption, 2024)
To transition towards sustainable mobility in emerging economies, fostering the use of electric vehicles (EVs) is required. This necessitates the development of an efficient management system for end-of-life (EoL) EV batteries under a circular economy principle. Using Thailand as a case study, this paper provides a holistic analysis by developing a Cost-Benefit Analysis (CBA) and deriving policy implications from the CBA results that consider stakeholder perspectives at the micro level and the uncertainties of future development. The findings suggest that the economies of scale (plant centralization) and the share of cathode chemistries play pivotal roles. In some cases, investment incentives may be required depending on the inflow of EoL batteries, technological advancements, and market volatility. A policy mix combining EoL volume-focused (i.e., enhancing battery collection rates/imports and establishing a clear policy roadmap for scaling up recycling operations) and monetary measures (i.e., taxes and financial subsidies) is essential to establish recycling facilities.
Created from Fastlane, Scopus look-up
Keywords: Circular economy; Cost-Benefit Analysis; Electric vehicle; Lithium-ion battery; Recycling; Sustainable mobility